Effectiveness of the “What’s Up!” Intervention to Reduce Stigma and Psychometric Properties of the Youth Program Questionnaire (YPQ): Results from a Cluster Non-randomized Controlled Trial Conducted in Catalan High Schools - Andrés-Rodríguez, Laura; Pérez-Aranda, Adrián; Feliu-Soler, Albert; Rubio-Valera, María; Aznar-Lou, Ignacio; Serrano-Blanco, Antoni; Juncosa, Miquel; Tosas, Anaïs; Bernadàs, Albert; Luciano, Juan V. (Frontiers in Psychology, 2017)
Mental disorders are highly prevalent in the general population, and people who experience them are frequently stigmatized. Stigma has a very negative impact on social, academic/professional, and personal life. Considering the high rates of mental disorders among children and adolescents (13.4%) and how critical this age is in the formation of nuclear beliefs, many campaigns to combat stigma have been developed in the last decade, with mixed results. The OBERTAMENT initiative has produced various anti-stigma campaigns in Catalonia (Spain). In the present study, the main objective was to report on the effectiveness of the OBERTAMENT “What’s up!” intervention, a curricular intervention including education and social contact conducted by the teachers in the classroom with teenagers aged between 14-18. Prior to this, we examined the psychometric properties of the Youth Program Questionnaire (YPQ), our main outcome measure, in terms of dimensionality, reliability, and validity. A cluster non-randomized controlled trial was conducted to assess this intervention, which was tested in 9 high schools situated in the Barcelona region. A convenience sample of 261 students formed the intervention group and 132 the control group (52% women, mean age= 14, SD= 0.47). The assignment to study conditions was conducted by Departament d’Ensenyament (Department of Education), Generalitat de Catalunya (Catalan Government). Participants were evaluated at baseline, post-intervention, and nine-month follow-up. The main outcome measure of this study was the YPQ. The Reported and the Intended Behaviour Scale (RIBS) was used as secondary outcome measure. The statistical analysis indicated that the YPQ possesses a two-factor structure (stereotypical attitudes and intended behavior) and sound psychometric properties. The multilevel mixed-effects models revealed statistically significant interactions for both study measures and post hoc intragroup analyses revealed a significant but small improvement in the YPQ and RIBS scores in the intervention group. Overall, our results indicate that “What’s up!” produced statistically significant, albeit small improvements in stereotypical attributions and intended behavior towards people with mental disorders. Some methodological limitations and the relatively low levels of stigma observed in our sample may undermine our results. The implications of our results are discussed in relation to stigma research.